Pengaruh Independensi, Pengalaman Kerja, Due Profesional Care, Dan Akuntabilitas Terhadap Kualitas Audit Dengan Etika Auditor Sebagai Variabel Pemoderasi(Studi Kasus Pada Kantor Akuntan Publik di Surakarta dan Yogyakarta) - Satiti, Satiti; Dr. Noer Sasongko, Dr. Noer Sasongko,SE, M.Si, Ak, CA (2016)
The purposes of this research to empirically analyze of independency, work experience, due professional care and accountability on audit quality, and to the influence of independency, work experience, due professional care and accountability to audit quality is moderated by auditor ethics, especially on auditors working on a public accountant office in region of Surakarta and Yogyakarta. The population in this research are all auditors who worked on the public accountant office in the region of Surakarta and Yogyakarta. Sampling was conducted using a purposive sampling method and number of samples of 57 respondents. Primary data collection method used is questionnaire method. The data are analyzed by using Moderate Regression Analyze (MRA). The result showed that the effect on the independency, work experience, due professional care, and accountability no effect on audit quality, but after being moderated by the ethics of auditors variable independency, work experience, due professional care, and accountability effect on audit quality, so it can be said that the ethics of auditors is moderating variables that are pure moderated. Keyword : Independency, Work Experience, Due Professional Care, Accountability, Auditors Ethich, Quality of Audit.